2020
DOI: 10.1111/ina.12758
|View full text |Cite
|
Sign up to set email alerts
|

Indoor heterogeneous photochemistry of furfural drives emissions of nitrous acid

Abstract: People spend approximately 80% of their time indoor, making the understanding of the indoor chemistry an important task for safety. The high surface-area-to-volume ratio characteristic of indoor environments leads the semi-volatile organic compounds (sVOCs) to deposit on the surfaces. Using a long path absorption photometer (LOPAP), this work investigates the formation of nitrous acid (HONO) through the photochemistry of adsorbed nitrate anions and its enhancement by the presence of furfural. Using a high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 79 publications
3
18
0
Order By: Relevance
“…Hence, indoor surfaces covered with molds can be a non‐negligible source of HONO mainly in sick buildings exhibiting large, contaminated areas, alongside high relative humidity, and low ventilation rates. Typical indoor levels are of the order of few ppbs 28,29,32 . These levels could significantly be affected by surface chemistry as it was previously demonstrated for various indoor surfaces 29,32,76 and for microbial indoor surface in the present work.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Hence, indoor surfaces covered with molds can be a non‐negligible source of HONO mainly in sick buildings exhibiting large, contaminated areas, alongside high relative humidity, and low ventilation rates. Typical indoor levels are of the order of few ppbs 28,29,32 . These levels could significantly be affected by surface chemistry as it was previously demonstrated for various indoor surfaces 29,32,76 and for microbial indoor surface in the present work.…”
Section: Resultssupporting
confidence: 71%
“…The mass spectrometry analysis of the mixed solution of molds extract and potassium nitrate showed the formation of some nitro and nitrogenated compounds during the film preparation. Depoorter et al 32 have also shown a possible nitration reaction during the preparation of furfural and potassium nitrate films. The authors have proposed a mechanism for the photochemical degradation of 2‐nitrofuran (a proxy for nitro compounds formed during the preparation of furfural films doped with KNO 3 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations